Analisis Higher Order Thinking Skills (HOTS) pada Soal Asesmen Madrasah pada Mata Pelajaran Al-Quran Hadis di MAN 3 Sleman - Taufikurohman, Mohammad; Maemonah, Maemonah (Jurnal Pendidikan Madrasah, 2024)
The purpose of this study is to examine how Higher Order Thinking Skills (HOTS) are applied in the Madrasah Assessment questions. A qualitative approach combined with descriptive analysis is the research methodology employed. Documentation and in-depth interviews were used to gather data. The analysis's findings indicate that, of the 35 questions examined, 33 belong to the HOTS category and just 2 to the LOTS category. Most of the questions fall into the C4 (analysing) and C5 (evaluating) cognitive levels of Bloom's Taxonomy, as updated by Anderson and Krathwohl. These results suggest that the evaluation at MAN 3 Sleman concentrates on helping students acquire higher-order thinking abilities, which is essential when studying the Qur'an and Hadith. This study does, however, also emphasize the necessity of maintaining a balance between LOTS and HOTS questions in assessments and the significance of continuous teacher preparation for creating HOTS questions. To guarantee the successful use of HOTS questions, legislators in the field of education must also provide their support. It is therefore intended that examinations will be more successful in equipping pupils with strong critical, creative, and analytical thinking abilities to meet problems in the future.